The DEAD-box protein Dbp6 is an ATPase and RNA annealase interacting with the peptidyl transferase center (PTC) of the ribosome. Issue 2 (5th January 2023) - Khreiss, Ali; Capeyrou, Régine; Lebaron, Simon; Albert, Benjamin; Bohnsack, Katherine E; Bohnsack, Markus T; Henry, Yves; Henras, Anthony K; Humbert, Odile
Abstract: Ribosomes are ribozymes, hence correct folding of the rRNAs during ribosome biogenesis is crucial to ensure catalytic activity. RNA helicases, which can modulate RNA–RNA and RNA/protein interactions, are proposed to participate in rRNA tridimensional folding. Here, we analyze the biochemical properties of Dbp6, a DEAD-box RNA helicase required for the conversion of the initial 90S pre-ribosomal particle into the first pre-60S particle. We demonstrate that in vitro, Dbp6 shows ATPase as well as annealing and clamping activities negatively regulated by ATP. Mutations in Dbp6 core motifs involved in ATP binding and ATP hydrolysis are lethal and impair Dbp6 ATPase activity but increase its RNA binding and RNA annealing activities. These data suggest that correct regulation of these activities is important for Dbp6 function in vivo . Using in vivo cross-linking (CRAC) experiments, we show that Dbp6 interacts with 25S rRNA sequences located in the 5′ domain I and in the peptidyl transferase center (PTC), and also crosslinks to snoRNAs hybridizing to the immature PTC. We propose that the ATPase and RNA clamping/annealing activities of Dbp6 modulate interactions of snoRNAs with the immature PTC and/or contribute directly to the folding of this region.